FREQUENCY OF ACUTE COMPLICATIONS OF HEMODIALYSIS IN ADULT AGE GROUP AT A TERTIARY CARE CENTER: Complications of Hemodialysis - Mahmood, Asif; Aziz, Kamran; Ahmed, Shahid; Baig, Zahid Farooq; Muhammad, Wasim Wali; Rahman, Muhammad Khalid (Pakistan Armed Forces Medical Journal, 2018)
Objective: To determine the frequency of acute complications of hemodialysis in adult age group at a tertiary care centre. Study Design: Descriptive study. Place and Duration of Study: Department of Medicine, Combined Military Hospital Lahore, from Apr 2012 to Oct 2012. Patients and Methods: We included 100 consecutive patients of chronic kidney disease on hemodialysis with age more than 12 years. Personal profile, comorbidities, intravenous access type and duration, hemodialysis parameters were recorded for each patient. Monitoring of blood pressure, temperature, pulse and history of palpitations, headache, nausea, vomiting, muscle cramps, fever, shivering, chest-pain, bleeding, fits, itching was recorded before and up till one hour post hemodialysis session. Results: In our study population fever was the commonest complication with frequency of 37%, followed by nausea and vomiting in 36%, muscle cramps in 28%, hypotension in 24%, headache in 23%, shivering in 22%, chest Pain in 15%, itching in 14%, hypertension in 10%, cardiac arrhythmias in 8%, hemorrhage in 7% and Seizures in 7% of patients. Conclusion: Infection related complications were more common in our set up as compared to international statistics which depicts that we should improve our antiseptic techniques.